Stage-wise management of Pakshaghata (Ischemic stroke with left hemiplegia) through ayurveda - A case report - Govardhan Belaguli; S A Nithin (Wolters Kluwer Medknow Publications, 2022)
In the context of Ayurveda, the condition Pakshaghata counters with hemiplegia and its variety of characteristic symptoms. The causes, pathogenesis and its management are well elucidated in Ayurveda. The following is a case report of an elderly male patient with Pakshaghata (Ischemic stroke with left hemiplegia) that was effectively treated on two different stages for nearly 56 days. His condition was divided into two stages, a) Margavaranajanya (~obstruction and adherence of other Doshas by the aggravated Dosha) stage, and b) Vatanulomana (~controlling of vitiated Vata dosha, bringing back to its normalcy) stage. The drugs that had the properties of Agnideepana (~neutralizers of the impaired metabolic fire), Amapachana (~metabolizers of undigested toxins), Srotoshodana (~evacuators of obstructed channels) and Vatanulomana were found effective in the first stage. As Vata Dosha (~one of bodily humors), is considered as the master controller of nervous system, and in order to bring it back to normal from the vitiated state, a set of drugs that had the property of Vatanulomana, Balya (~strength promoters) and Rasayana (~rejuvenators) were induced in the second stage. There was a significant improvement in his degree of disability as per Scandinavian stroke score, Barthel Index score and Modified Rankin Scale; it measured 51, 65 and 3 respectively after the intervention (from 16, 0 and 5 prior to intervention). Through this study, it can be planned that, the treatment protocol of Pakshaghata can be judged by the acute and chronic phase of the condition based on its association with Vata dosha. The wise selection of the appropriate drugs and therapies in the present case secured the optimistic outcome of the intervention. Although his concluding magnetic resonance imaging of brain notified "no" modifications, at the time of discharge he was privileged with refurbished gait; sensory and motor deficits with increased quality of life, which prompted us to document it.